Pengaruh Harga Saham Sebelumnya, Indeks Harga Saham Individual, Net Profit Margin, Dan Debt To Equity Ratio Terhadap Stock Returns (Studi Empiris Perusahaan Consumer Goods Berlaba Negatif yang Terdaftar di Bursa Efek Indonesia Antara Tahun 2019 - 2021) - Nugroho Agung Prakoso; Muhammad Nasim Harahap (Jurnal Ilmiah Wahana Pendidikan, 2023)
Stocks differ from investing in bonds in that they represent a fractional ownership of equity in a company. Consistent research can help investors identify the best opportunities to buy low and sell high and maximise profits over the long term. Both technical analysis and fundamental analysis can be used to analyse stock returns. This study aims to determine or investigate the effect of the previous stock price, individual stock price index, net profit margin, and debt to equity ratio on stock returns in negative profit consumer goods companies listed on the Indonesia Stock Exchange in 2019-2021. From a population of 64 firms, 11 companies were chosen as samples. The relationship between variables was analysed using the multiple regression model, which resulted in findings that the previous stock price variable, individual stock price index, net profit margin, and debt to equity ratio simultaneously did not have a significant effect on stock returns. Partially, stock returns are not significantly affected by the previous stock price, net profit margin, and debt to equity ratio. However, the individual stock price index significantly affects stock returns for negative-profit consumer goods companies listed on the Indonesia Stock Exchange in 2019-2021.